Abnormal Brain Perfusion in Autism Spectrum Disorder: Evidence from Radionuclide SPECT Imaging (Bangladesh Journal of Nuclear Medicine, 2026)
Background: Autism Spectrum Disorder (ASD) is a neurodevelopmental condition with increasing prevalence worldwide. Identifying cerebral perfusion abnormalities may provide objective biomarkers for diagnosis and therapeutic monitoring. Objective: To evaluate regional cerebral blood flow (rCBF) abnormalities in children with ASD using Tc-99m ECD Brain SPECT and assess their correlation with clinical severity. Methods: A cross-sectional study was conducted at the National Institute of Nuclear Medicine & Allied Sciences (NINMAS), Dhaka. A total of 34 children (3–12 years) with clinically confirmed ASD were included. Participants underwent 99m Tc- ECD Brain SPECT, and perfusion abnormalities were analyzed using Z-scores. Severity was classified according to Autism Diagnostic Checklist (ADCL) scores. Statistical analysis was performed using SPSS v26, with p ≤ 0.05 considered significant. Results: Hypoperfusion was observed across multiple cortical regions. In mild ASD, hypoperfusion occurred in the frontal (100%), temporal (80%), and parietal (70%) cortices. Low-moderate ASD demonstrated widespread perfusion deficits, particularly in frontal (100%) and temporal (90%) regions. High-moderate ASD cases exhibited marked hypoperfusion in parietal (100%) and frontal (85%) regions. Symptom analysis revealed strong associations: speech delay (93%) correlated with frontal (98%) and temporal (88%) hypoperfusion; hyperactivity (68%) with frontal (100%) and temporal (85%) hypoperfusion; and cognitive dysfunction with frontal and parietal hypoperfusion. ADCL scores positively correlated with Z-scores (ρ = 0.609, p = 0.002). High-moderate ASD cases showed significantly elevated Z-scores compared to mild and low-moderate groups (p < 0.05). Conclusion: Abnormal cerebral perfusion, particularly hypoperfusion in the frontal, temporal, and parietal cortices, is strongly associated with ASD severity and core clinical symptoms. Tc-99m ECD Brain SPECT may serve as a valuable adjunctive tool for early diagnosis, severity stratification, and therapeutic monitoring in ASD.Bangladesh J. Nuclear Med. 28(2): 336-343, July 2025